(untitled) (Cardiovascular Journal, 2014)
Background: Treatment of Congenital Heart Disease (CHD) is either Surgical or Interventional. Medical management is mainly symptomatic / palliative. Although surgery is the main mode of treatment but in the recent past non-surgical Interventional method is replacing it because of its multiple advantages over surgical procedures. Since 2005, we started our journey in National Institute of Cardiovascular Diseases with a PDA device closure. In this article we tried to review the success rate of the interventional procedures in this hospital. Methods: The aim of this retrospective study is to review the short term & Intermediate outcome of the non surgical interventional treatment of congenital heart diseases. We included all the interventional rocedures done in this Institute since 2005 upto December 2013. Results: During this period, we performed total 150 cases of patent ductus arteriosus (PDA) device, 20 cases of PDA Coil closure, 60 cases of atrial septal defect (ASD) device, 90 cases of Balloon Pulmonary Valvuloplasty (BPV), 20 cases of Balloon Aortic Valvuloplasty (BAV), 22 cases of Coarctation Balloon Angioplasty, 35 cases of Mitral Valvuloplasty (PTMC), 15 cases of Balloon Atrial Septostomy. Almost all of our intervention procedures were successful except one case of mortality related to procedure of PDA device closure, 4 device embolization (2 ASD & 2 PDA) and one case of PDA coil with persistent Intravascular hemolysis. All the embolized devices were subsequently retrieved surgically with repair. All other patients of interventional treatment are enjoying new life without any morbidity. Conclusion: Thus, we concluded that interventional methods of suitably selected case of congenital heart disease may be an alternative lucrative safe & effective option of remedy for many of the congenital heart diseases. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18354 Cardiovasc. j. 2014; 6(2): 133-142